TFEB: A Emerging Regulator in Lipid Homeostasis for Atherosclerosis - Li, Manman; Wang, Zitong; Wang, Pengyu; Li, Hong; Yang, Liming (Frontiers in Physiology, 2021)
Atherosclerosis, predominantly characterized by the disturbance of lipid homeostasis, has become the main causation of various cardiovascular diseases. Therefore, there is an urgent requirement to explore efficacious targets that act as lipid modulators for atherosclerosis. Transcription factor EB (TFEB), whose activity depends on post-translational modifications, such as phosphorylation, acetylation, SUMOylation, ubiquitination, etc., is significant for normal cell physiology. Recently, increasing evidence implicates a role of TFEB in lipid homeostasis, via its functionality of promoting lipid degradation and efflux through mediating lipophagy, lipolysis, and lipid metabolism-related genes. Furthermore, a regulatory effect on lipid transporters and lipid mediators by TFEB is emerging. Notably, TFEB makes a possible therapeutic target of atherosclerosis by regulating lipid metabolism. This review recapitulates the update and current advances on TFEB mediating lipid metabolism to focus on two intracellular activities: a) how cells perceive external stimuli and initiate transcription programs to modulate TFEB function, and b) how TFEB restores lipid homeostasis in the atherosclerotic process. In-depth research is warranted to develop potent agents against TFEB to alleviate or reverse the progression of atherosclerosis.